Isolasi dan Aktivitas Antioksidan Fraksi dari Ekstrak Tongkol Jagung - Edi Suryanto; Lidya Irma Momuat (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
The corn cob is one of the food waste-material having phytochemical component that of health benefit. The objectives of the research were to isolate phenolic fractions of the corn cob extract and to determine antioxidant and antiphotooxidant activities. The corn cob was extracted with reflux method using ethanol 80% for 2 hours. After that the extracts were filtered and the filtrates were combined and concentrated on rotary evaporator. This crude ethanolic extract was suspended in water and extracted with petroleum ether, ethyl acetate, n-butanol and water, respectively. The best fractions of partition fractionated with colomn chromatography using silica gel 60 and n-hexane: ethyl acetate (4:6). Corncob extract and fraction were evaluated for total phenolic content free radical scavenging activity (1,1-diphenyl-2-picrylhydrazyl radical assay) and total antioxidant capacity (ferric reducing ability of plasma assay). The results of total phenolic content showed that ethyl acetate fraction (163.57 μg/mL) has higher phenolic content than butanol fraction (83.30 μg/mL), ethanol extract (81.53 μg/mL), water fraction (23.71 μg/mL) and petroleum ether fraction (23.57 μg/mL). The results also showed that ethyl acetate fraction has highest free radical scavenging activity and total antioxidant capacity than butanol fraction, ethanol extract, water fraction and petroleum ether fraction. The free radical scavenging activity of fractions II and III exhibited strongest activity than fraction V, I, IV and VI. The results also showed that fraction II has highest total antioxidant capacity than I, III, IV, VI, and V. The results suggest that the ethyl acetate fraction and fraction II contains phenolic compounds which possess antioxidant activities. ABSTRAKTongkol jagung merupakan salah satu limbah tanaman pangan yang mempunyai kandungan fitokimia yang bermanfaat untuk kesehatan. Penelitian ini bertujuan untuk mengisolasi fraksi fenolik dari ekstrak tongkol jagung dan menentukan aktivitas antioksidan. Tongkol jagung diekstraksi dengan cara refluk menggunakan etanol 80% selama 2 jam. Setelah itu disaring dan filtratnya diuapkan dengan rotary evaporator. Ekstrak etanol disuspensikan dalam air dan diekstraksi berturut turut dengan petroleum eter, etil asetat, butanol, dan air. Fraksi pelarut terbaik difraksinasi dengan kromatografi kolom menggunakan silika gel 60 dan eluen n-heksana : etil asetat (4:6). Ekstrak tongkol jagung dan fraksi dievaluasi kandungan total fenolik, aktivitas penangkal radikal bebas (uji 1,1-difenil-2-pikrilhidrazil) dan kapasitas total antioksidan (uji ferric reducing ability of plasma). Hasil uji kandungan total fenolik menunjukkan bahwa fraksi etil asetat (163,57 μg/mL) memiliki kandungan total fenolik yang paling tinggi daripada fraksi butanol (83,30 μg/mL), ekstrak etanol (81,53 μg/mL), fraksi air (23,71 μg/mL) dan fraksi petroleum eter (23,57 μg/mL). Hasil ini juga menunjukkan bahwa fraksi etil asetat mempunyai aktivitas penangkal radikal dan kapasitas total antioksidan paling tinggi daripada fraksi butanol, ekstrak etanol, fraksi air, dan fraksi petroleum eter. Aktivitas penangkal radikal bebas fraksi II dan III memperlihatkan paling kuat daripada fraksi V, I, IV dan VI. Hasil penelitian ini menyarankan bahwa fraksi etil asetat dan fraksi II mengandung senyawa fenolik yang mempunyai aktivitas antioksidan kuat.